Step-by-step explanation:
In a right angle triangle one angle is 90°
w.k.t sum of angles in a triangle is 180°
thus, 2x+15+x+90°=180°
3x+105°=180°
3x=75°
x= 75/3=25°
Hope this helps you.
F(x) = 3x^2+6x-2
= 3(x^2+2x-2/3)
= 3(x^2 +2x + 1 - 1 - 2/3)
= 3((x+1)^2 - 1 - 2/3)
= 3((x+1)^2 -5/3))
= 3(x+1)^2 - 5
So our function is in the form:
f(x) = 3(x+1)^2 - 5
where a = 3, h = -1, k = -5
Answer:
answer 1/2
Step-by-step explanation:
y-3=-2(x-4)
y-3=-2x+8
y=-2x+11
y=mx+c
m= slope which is -2
because it perpendicular It became 1/2
Multiply 60 by .75, which gives you 45 Points. The answer is B.